Republic of Korea : 2009 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Korea. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This 2009 Article IV Consultation highlights that like other open economies, Korea was hard hit by the global financial crisis during the last quarter of 2008. The authorities responded with a timely and comprehensive set of financial market and macrostabilization measures. Executive Directors have commended the authorities for their speedy and comprehensive measures, which have successfully stabilized the economy and the financial system. Directors have also supported the sizable and frontloaded fiscal stimulus package and the intention to maintain fiscal stimulus in 2010 given the uncertain outlook.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet